PEMBERDAYAAN CIVITAS AKADEMIKA DALAM MENCIPTAKAN LINGKUNGAN BERSIH MELALUI KERJA SAMA KOLEKTIF - Roidatus Shofiyah; Rifda Arifa Sani; Rahayu Mardikaningsih; Laili Mas Ulliyah Hasan; Yeni Vitrianingsih (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service program aims to enhance awareness and active participation of the academic community at Sunan Giri University Surabaya in creating a clean, healthy, and sustainable campus environment through collective collaboration. The program was conducted from November to December 2025 by transforming unused vacant land within the campus area. The Asset-Based Community Development (ABCD) approach was employed, emphasizing the utilization of internal assets such as human resources, social capital, and physical environmental potential. Activities included socialization sessions, collective clean-up actions, reuse of waste materials, planting of ornamental and food crops, and strengthening solidarity through collaborative activities. The results indicate increased collective awareness of environmental cleanliness, strengthened shared responsibility, and the creation of green campus spaces that support a conducive learning environment. This program demonstrates a sustainable community engagement model that positions the campus as a living laboratory grounded in collaboration and environmental sustainability.